Le maître d'oeuvre sur un chantier de construction - Napert, René; Darveau, François (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1988)
The construction industry is a prime area for workplace accidents and as such The Health and Occupational Safety Act devotes an entire chapter to the subject. The objective of suppressing danger at its source has required making the foreman the most important agent for looking after the health and well-being of workers. Based on caselaw, this article focuses on sharpening the notion of the foreman acting in the workplace within the framework of The Health and Occupational Safety Act. Two major aspects are developed : that of the identification of the foreman and his obligations on a construction site.